2011
DOI: 10.1371/journal.pone.0028518
|View full text |Cite
|
Sign up to set email alerts
|

A Metabolic Index of Ischemic Injury for Perfusion-Recovery of Cadaveric Rat Livers

Abstract: With over 110,000 patients waiting for organ transplantation, the current crisis in organ transplantation is based on a lack of donors after brain-death (DBD). A very large alternative pool of donor organs that remain untapped are the donors after cardiac death (DCD), recovered after cardiac activity has ceased and therefore sustained some ischemic injury. Machine perfusion has been proposed as a novel modality of organ preservation and treatment to render such cadaveric organs, and in particular livers, trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 45 publications
0
31
1
Order By: Relevance
“…It has been demonstrated by other investigators that large quantities of phenylalanine and tyrosine were detected in patients with liver injury and these amino acids were specifically released in the patients of liver injury. 21,22) Significant correlations were observed between phenylalanine and tyrosine concentrations and total bilirubin levels and albumin levels. Serum phenylalanine and tyrosine concentrations correlated well with imaging and laparotomy findings of liver injury.…”
Section: Resultsmentioning
confidence: 96%
“…It has been demonstrated by other investigators that large quantities of phenylalanine and tyrosine were detected in patients with liver injury and these amino acids were specifically released in the patients of liver injury. 21,22) Significant correlations were observed between phenylalanine and tyrosine concentrations and total bilirubin levels and albumin levels. Serum phenylalanine and tyrosine concentrations correlated well with imaging and laparotomy findings of liver injury.…”
Section: Resultsmentioning
confidence: 96%
“…For example, it has been proposed by the National Heart Lung and Blood Institute and found by other studies that many hearts that would provide substantial survival benefits to patients are going unused, largely owing to a lack of reliable methods to assess their suitability for transplantation 79,92 . By allowing organ function to be observed after procurement, perfusion platforms are enabling the investigation of new biomarkers that predict organ health and transplantability 9396 .…”
Section: Organ Transplantation Without Preservation Constraintsmentioning
confidence: 99%
“…A few studies have reported reclamation of DCD grafts exposed to 60-min warm ischemia. Peaks et al and Tolboom et al successfully rescued almost all transplants that underwent 60-min warm ischemia by normothermic extracorporeal perfusion (2,31). In terms of survival, after 60-min warm ischemia, VSOP-NO appeared to be inferior to machine perfusion.…”
Section: Discussionmentioning
confidence: 99%